Dillenia nagalim (Dilleniaceae): a new species based on morphological and molecular characters from Manipur, Northeast India - Kashung, Sochanngam; Leishilembi, Urikkhimbam; Kaini, Kholi; Maheo, Rachel Sochui; Rupa, Tilling; Kashung, Gladyso; Gangmei, Kerene; Lokho, Kreni; Eshuo, Kazhuhrii (Phytotaxa, 2026)
Dillenia nagalim (Dilleniaceae), a new species, has been described from Manipur, Northeast India. The newly described species shows close morphological similarity to D. pentagyna and D. hookeri but differs from the latter in having a short habit of 2–4 feet tall, an amplexicaul short petiole, leaves with double serrate margins, an acuminate leaf apex, showy flowers, numerous stamens, and 7–8 carpels. We have highlighted the diagnostic morphological characters, colour photographs, phenology, conservation status, and artificial keys for easy identification. Molecular phylogenetic analysis based on the rbcL gene supports it as a new species. The discovery of this new species highlights the phytogeographical importance of the region situated within the Indo-Burma biodiversity hotspot, where anthropogenic activities are intense and considered as “vulnerable (VU D2)” under the IUCN Red List Categories and Criteria.